2016
DOI: 10.1111/papr.12467
|View full text |Cite
|
Sign up to set email alerts
|

Metamizole (Dipyrone) as an Alternative Agent in Postoperative Analgesia in Patients with Contraindications for Nonsteroidal Anti‐Inflammatory Drugs

Abstract: Although firm evidence is lacking, metamizole may be safer for the upper intestinal tract and kidneys than other NSAIDs, and could alternatively be used in patients with an increased risk for stomach or renal problems. Hereby, improved postoperative pain relief can potentially be achieved. The risk for metamizole-induced agranulocytosis is judged to be acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 17 publications
0
38
0
10
Order By: Relevance
“…Apart from its efficacy, one particular advantage of dipyrone compared to NSAIDs is its apparent lack of any teratogenic adverse effects . It is particularly suitable for those in whom NSAIDs are contraindicated or pose a greater risk . It has remained a popular analgesic not only because it is effective but also is generally safer than NSAIDs and opioids and cheap.…”
Section: Commentmentioning
confidence: 99%
“…Apart from its efficacy, one particular advantage of dipyrone compared to NSAIDs is its apparent lack of any teratogenic adverse effects . It is particularly suitable for those in whom NSAIDs are contraindicated or pose a greater risk . It has remained a popular analgesic not only because it is effective but also is generally safer than NSAIDs and opioids and cheap.…”
Section: Commentmentioning
confidence: 99%
“…However, these studies, when applying the Jadad score, were classified as poor, making definite conclusions impossible. A recent literature review in adults suggested that, although firm evidence is lacking, the use of dipyrone in patients with an increased risk of gastrointestinal bleeding and/or renal disease may be safer than other NSAIDs …”
Section: Discussionmentioning
confidence: 99%
“…The reason of this divergence is the nonenzymatic hydrolysis of metamizole in the gastrointestinal tract to its first metabolite, 4‐methylaminoantipyrine (4‐MAA), leading to its fast and nearly complete absorption when given orally. Mediated by its active metabolites, metamizole achieves an oral bioavailability of almost 100% . Following the results of a small study published decades ago, it was assumed that food intake does not influence the absorption of metamizole.…”
Section: Hepatic Metabolism Of Metamizolementioning
confidence: 99%
“…Mediated by its active metabolites, metamizole achieves an oral bioavailability of almost 100%. [57][58][59] Following the results of a small study published decades ago, it was assumed that food intake does not influence the absorption of metamizole. In this trial in 12 healthy male volunteers aged between 24 and 30 years, metamizole was delivered once after fasting for 8 hours and once immediately after a breakfast standardized within the study.…”
Section: Hepatic Metabolism Of Metamizolementioning
confidence: 99%